Radicalization Through the Lens of Situated Affectivity - Haq, Hina; Shaheed, Saad; Stephan, Achim (Frontiers in Psychology, 2020)
Affective bonding to radical organizations is one of the most prominent features of a recruit’s personality. To better understand how affective bonding is established during the recruitment of youth for radicalization and how it is maintained afterward, it seems promising to adopt new insights and developments from the field of situated cognition and affectivity, particularly the concepts of Affective Scaffolding, Mind Invasion, and Self-Stimulatory Loops of Affectivity (SSLA). The three notions highlight both the intended structuring of the affective bonding by the recruiting organizations and the immersive influence these settings have on the individuals. We will study the affective bonding between an individual and a radical group from two perspectives: first, from an organizational perspective, and second from a personal perspective. The first aims at understanding how extremist organizations “invade the mind” of young people, by providing carefully designed affective scaffolding: (a) during the recruitment process and (b) while being a full member of the organization. The second aims at identifying some of the affective loops which individuals who have joined the radical organization enter.